Synthesis and Screening of Antidiabetic Activity of Some Novel Curcumin Analogues - SURESH KONATHAM; PRANEETH KUMAR; JITHAN AUKUNURU (International Journal of Pharma and Bio Sciences, 2010)
Curcumin is a major constituent of turmeric. It possesses divergent pharmacological activities like anti inflammatory, antioxidant, anticancer, anti HIV, hepatoprotective, and anti diabetic activities etc. Curcumin structural analogues were synthesized and reported to possess same or superior activity compared to the Curcumin. Analogues were synthesized using different aromatic substituted aldehydes and they were characterized using spectral data (FTIR, NMR). All the synthesised compounds were screened for anti diabetic activity. From all the six compounds synthesized, compound II and compound III showed highly significant activity than curcumin and are comparable to standard drug glibenclamide. From the six compounds synthesized, four compounds I, II, III, and VI showed superior in antidiabetic activity compared to curcumin and other two compounds IV and V are inferior in antidiabetic activity compared to curcumin. Compound II was equal in activity compared to the standard drug glibenclamide.